Characterisation of regional skin temperatures in recreational surfers wearing a 2-mm wetsuit. Issue 5 (4th May 2018) - Corona, Luis J.; Simmons, Grant H.; Nessler, Jeff A.; Newcomer, Sean C.
Abstract: The purpose of this study was to investigate skin temperatures across surfers' bodies while wearing a wetsuit during recreational surfing. Forty-six male recreational surfers participated in this study. Participants were instrumented with eight wireless iButton thermal sensors for the measurement of skin temperature, a Polar RCX5 heart rate monitor and a 2-mm full wetsuit. Following instrumentation, participants were instructed to engage in recreational surfing activities as normal. Significant differences ( p < 0.001) in skin temperature ( T sk ) were found across the body while wearing a wetsuit during recreational surfing. In addition, regional skin temperature changed across the session for several regions of the body ( p < 0.001), and the magnitude of these changes varied significantly between regions. We show for the first time that significant differences exist in skin temperature across the body while wearing a wetsuit during a typical recreational surfing session. These findings may have implications for future wetsuit design. Practitioner Summary: This study investigated the impact of wearing a wetsuit during recreational surfing on regional skin temperatures. Results from this study suggest that skin temperatures differ significantly across the body while wearing a 2-mm wetsuit during recreational surfing. These findings may have implications for future wetsuit design.